Diversity, distribution and relative abundance of the mosquito fauna (Diptera: Culicidae) of Malakand and Dir Lower, Pakistan - Attaullah,M. (2023)
Abstract The present study was conducted to evaluate the diversity, distribution (C) and relative abundance (RA) of the mosquito fauna (Diptera: Culicidae) of Malakand and Dir Lower, Pakistan. Collection of specimens (n = 1087) was made during September 2018 to July 2019 at six different habitats including freshwater bodies, rice fields, animal sheds, indoors, drains and sewage waters. Specimens were collected through light traps, pyrethrum spray, aspirators and nets and subsequently killed, preserved and then arranged in entomological boxes for identification. Three genera were identified namely Culex, Anopheles and Aedes. A total of fourteen species were identified namely: Cx. quinquefasciatus (Say, 1823), An. stephensi (Liston, 1901), Cx. tritaeniorhynchus (Giles, 1901), Ae. vittatus (Bigot, 1861), An. maculatus (Theobald, 1901), An. fluviatilis (James, 1902), Cx. vishnui (Theobald, 1901), Ae. aegypti (Linnaeus, 1762) An. subpictus (Grassi, 1899), An. dthali (Patton, 1905), An. culicifascies (Giles, 1901), An. pallidus (Theobald, 1901), Ae. albopictus (Skuse, 1894) and An. annularis (van der Wulp, 1884). Cx. quinquefasciatus was found constantly distributed in the study area with RA = 16.5% and C = 100%. An. annularis was found as a satellite species, sporadically distributed in the study area having RA = 0.9% and C = 17%. Diversity indices of mosquitoes in the studied habitats were found as, Shannon-Wiener Index (2.415), Simpson Index (9.919), Fisher’s Index (2.269) and Margalef’s Index (1.859). A statistically significant difference was recorded in mosquito diversity in the six habitats (Kruskal-Wallis, chi-squared, H = 17.5, df = 5, P = 0.003 at α = 0.05). The present study encompasses mosquito fauna of Malakand, Pakistan with respect to diversity, relative abundance and distribution in diverse habitats and all seasons of the year. This will assist scientists working in various fields related with epidemiology, medical and veterinary entomology, ecology and allied areas of biological sciences.